THE NEUROPROTECTIVE EFFECT OF ELECTRO-ACUPUNCTURE AGAINST ISCHEMIC STROKE IN ANIMAL MODEL: A REVIEW - Feng, Rui; Zhang, Feng (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: It is well established that electro-acupuncture can exert neuroprotection in animal experiments. However, the exact mechanism of electro-acupuncture against ischemic stroke is not very clear. Materials and methods: Literature retrieval was performed in four databases (OVID, PUBMED, EMBASE, and ISI Web of Science), from respective inception to July 2013. Results: Series of studies have demonstrated that electro-acupuncture might be a promising method in reducing brain damage after stroke and induce brain ischemic tolerance before stroke through the promotion of angiogenesis, alleviation of the inflammatory response, regulation of the blood brain barrier (BBB), inhibition of apoptosis, and so on. Through these mechanisms, electro-acupuncture may reduce the neural damages associated with stroke. Conclusion: An awareness of the benefits of acupuncture might lead more patients into accepting acupuncture therapy for the management of patients with ischemic stroke and patients with high risk of ischemic stroke.